Method and Apparatus of Measuring Velocity and Sound Attenuation Coefficient in Bulk Materials Based on the Analysis of the Structure of Sound-Insulation Materials on the Basis of Perlite; IOP Conference Series: Materials Science and Engineering; Vol. 189 : Modern Technologies for Non-Destructive Testing - Kapranov B. I. Boris Ivanovich (2017, 2017)
Title screen